2013
DOI: 10.1371/journal.pntd.0002277
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Diagnostic Value of Serial Daily Bedside Ultrasonography for Severe Dengue in Indonesian Adults

Abstract: BackgroundIdentification of dengue patients at risk for progressing to severe disease is difficult. Significant plasma leakage is a hallmark of severe dengue infection which can suddenly lead to hypovolemic shock around the time of defervescence. We hypothesized that the detection of subclinical plasma leakage may identify those at risk for severe dengue. The aim of the study was to determine the predictive diagnostic value of serial ultrasonography for severe dengue.Methodology/Principal FindingsDaily bedside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 17 publications
3
54
0
4
Order By: Relevance
“…However, a previous study reported that an increase in hematocrit of ≥20% is not sensitive for detecting plasma leakage and that it occurred infrequently in severe dengue. (6,9,15) Suwarto et al (7) showed that the cut-off point for hemoconcentration of ≥15.1% is a better predictor of plasma leakage and minimizes the risk of under-diagnosing patients who are at risk for developing severe dengue. In the present study, we suggest a similar cut-off point as the previous study, (7) which is ≥15.625%, as a risk factor for severe dengue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a previous study reported that an increase in hematocrit of ≥20% is not sensitive for detecting plasma leakage and that it occurred infrequently in severe dengue. (6,9,15) Suwarto et al (7) showed that the cut-off point for hemoconcentration of ≥15.1% is a better predictor of plasma leakage and minimizes the risk of under-diagnosing patients who are at risk for developing severe dengue. In the present study, we suggest a similar cut-off point as the previous study, (7) which is ≥15.625%, as a risk factor for severe dengue.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criterion was incomplete data in medical records. The sample size was calculated using the formula for the difference between two population means by estimating the hematocrit population variance of 1.64, (9,10) assuming a difference in the population mean of 0.5. With 80% power to detect a 5% difference, the minimum total sample size required was 206 patients.…”
Section: Research Subjectsmentioning
confidence: 99%
“…Effusions detected by US (pleural, pericardial, and ascitic) have been described as signs of plasma leakage in children 84 and adults 85 with dengue infection. The presence of effusions correlated with progression to more severe forms of the disease (dengue hemorrhagic fever (DHF), dengue shock syndrome), and its negative predictive value was found to be very high.…”
Section: Other Infectious Diseases With Potential For Pocus Applicationmentioning
confidence: 99%
“…The presence of effusions correlated with progression to more severe forms of the disease (dengue hemorrhagic fever (DHF), dengue shock syndrome), and its negative predictive value was found to be very high. 85 Gallbladder wall thickening 85,86 and subcapsular splenic and hepatic fluid collections 87 have also been reported as signs of plasma leakage. It has been suggested that during a dengue epidemic, the diagnosis of DHF should be considered when US demonstrates gallbladder wall thickening, ascites, splenomegaly, and pleural effusion in a febrile patient with thrombocytopenia.…”
Section: Other Infectious Diseases With Potential For Pocus Applicationmentioning
confidence: 99%
“…(7,8) Plasma leakage resulting in tissue hypoxia is determined from the hematocrit (ht) and plasma protein concentration (especially albumin), and from the presence of pleural effusion and/or ascites upon imaging, using both plain X-rays of the thorax and ultrasonography of the abdomen. (9)(10)(11)(12) The study of Santosa et al (11) on children with hemorrhagic fever showed an increase in the hematocrit of 20% or higher, which value is currently considered to indicate the occurrence of significant plasma leakage, and was found to correspond to a serum lactate level of >2.4 mmol/ L (sensitivity 79.31%, specificity 77.42%). The conclusion of abovementioned study was that serum lactate level may be used to determine the occurrence of significant plasma leakage in children with dengue hemorrhagic fever.…”
Section: Introductionmentioning
confidence: 99%